2002
DOI: 10.1073/pnas.112604099
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a dysfunctional prefrontal circuit in patients with an impulsive aggressive disorder

Abstract: Humans with lesions to the orbital͞medial prefrontal cortex and interconnected areas display impulsive aggressive behavior. To examine further the relationship between impulsive aggression and orbital͞medial prefrontal dysfunction, we measured the behavioral performance of psychiatric patients with a disorder characterized by impulsive aggression, Intermittent Explosive Disorder (IED). Presently, no evidence exists for a localized brain lesion in IED subjects. However, on the basis of the location of brain les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
157
4
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(177 citation statements)
references
References 48 publications
11
157
4
5
Order By: Relevance
“…In IED, cognitive deficits appear to be circumscribed to affective and social domains but are relative, not absolute deficits of function in these domains (Best et al, 2002) and are not associated with lower intelligence (Best et al, 2002). These findings suggest that the underlying neural abnormality is more subtle than that encountered in disconnection syndromes caused by gross lesions or neurodevelopmental disorders.…”
Section: Introductionmentioning
confidence: 66%
“…In IED, cognitive deficits appear to be circumscribed to affective and social domains but are relative, not absolute deficits of function in these domains (Best et al, 2002) and are not associated with lower intelligence (Best et al, 2002). These findings suggest that the underlying neural abnormality is more subtle than that encountered in disconnection syndromes caused by gross lesions or neurodevelopmental disorders.…”
Section: Introductionmentioning
confidence: 66%
“…Statistical parametric maps (SPMs) were produced from linear contrasts of interest: each face category versus baseline (eg, angry4fixation) and all faces4fixation. We opted for this latter contrast to use in the group-level analyses for several reasons: (1) because of the application of high-pass filtering, condition (face expression)-specific effects are partly removed; (2) amygdala activation to the 'neutral' expressionless faces have been shown to also activate the amygdala to the same extent as emotional faces (Fitzgerald et al, 2006); and (3) IED subjects have been shown to mislabel 'neutral' faces as conveying negative emotions (Best et al, 2002). To test whole-brain voxel-wise effects, a full-factorial model was set up in SPM.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IED patients showed less amygdala-orbitofrontal cortex connectivity than controls, suggesting reduced regulatory control of the prefrontal cortex. Previous work already showed that IED patients make disadvantageous choices on the Iowa gambling task, hinting at the possibility of disrupted prefrontal functioning (Best et al, 2002). The limited available research on the neural systems underlying IED so far thus points at a disrupted amygdala-prefrontal circuitry, yet a complex disorder like IED undoubtedly involves an even broader network of brain regions.…”
Section: Introductionmentioning
confidence: 99%
“…5-HT neurons project from the dorsal raphé (DRN) to the PFC and there has been increasing evidence that dysfunctions in these neurons may underlie impulsive behavior and aggression (Grafman et al, 1996;Bechara et al, 2000;Brower and Price, 2001;Chudasama et al, 2003;Best et al, 2002;Spinella, 2004). For these reasons, presynaptic 5-HT 1B receptors located in this region might be important modulators of Alc-heightened aggression.…”
Section: Introductionmentioning
confidence: 99%